Dental prosthesis and buccal lesions in the elderly - Beatriz García Alpizar; Mikhail Benet Rodíguez; Eduardo Enrique Castillo Betancourt (Medisur)
Fundament: Buccal lesions in the elderly are very frequent and they constitute a problem of health due to the consequences that cause. Objective: to describe the characteristics of the removable prosthesis used by the population of 60 and more years age and their relationship with the lesions of the oral mucosa. Methods: We carried out a study descriptive of cross section in 125 elderly with oral prosthesis. The characteristics of the removable prosthesis were described and their relationship with the lesions of the oral mucosa. The square chi tests and the analysis of relative risk were use to determine the association between the variables, also we used a logistical regression model to determine the independent relationship of each factor with the presence of the lesions. Results: We was a 12% of the people with stomatitis sub prosthesis, 8% presented lesions growth hyperplasic and 5,6% they were have angular queilitis. The lesions in the oral mucosa increased in people with prosthesis in not well state, bad hygiene this and in the female sex. Conclusion: the chronic lesions were the more prevalence in this study and they were very related with factors like: state of the conservation the prosthesis, time use, hygiene this and sex of the individual; but when determining the independent influence from each factor with the presence lesions, we established that only the state of conservation of the prosthesis and their hygiene affected of the important way to the old men of this study.